The Effects of Children’s Smartphone Addiction on Sleep Duration: The Moderating Effects of Gender and Age - Yoon, Ji-Yeon (Int J Environ Res Public Health, 2021)
Background: Smartphones are an important part of children’s and adolescents’ lives, and they often spend a lot of time using them. This study aims to precisely discover the effects of smartphone addiction on sleep duration as moderated by age and gender. Materials and methods: The data utilized in this study are from the ‘Korean Children and Youth Panel Survey 2018′ by the National Youth Policy Institute; a total of 4940 youths (2399 in grade 4 and 2541 in grade 7) from the survey were analyzed by Stata 15.0 S. The dependent variable is sleep duration, and the independent variables are the sub-factors of smartphone addiction: disturbance of adaptive functions, virtual life orientation, withdrawal, and tolerance. An independent t-test was conducted to confirm the differences in the main variables according to gender and age. Multiple regression analysis was conducted to verify the moderating effects of gender and age in the relationship between children’s smartphone addiction and sleep duration. Results: First, the average sleep duration among grade 4 students was 9.17 h and grade 7 students was 7.96 h. Second, sleep duration was significantly higher for males than females, while there was no difference in smartphone addiction by gender. Third, smartphone addiction, particularly the sub-factor of tolerance significantly affected sleep duration. Fourth, age significantly affected sleep duration and gender had a moderating effect on sleep duration. Conclusions: Interventions to develop a healthy smartphone usage culture on family and societal levels would be beneficial for increasing awareness of smartphone addiction and its adverse effects on children and adolescents. Furthermore, targeted intervention would be more effective at modifying addictive behavior and sleep duration than trying to administer blanket interventions to youths as a whole.